Evidence of active herpesvirus 6 (variant-A) infection in patients with lymphadenopathy in Belém, Pará, Brazil - Ronaldo B. Freitas; Maria R. Freitas; Alexandre C. Linhares (Revista do Instituto de Medicina Tropical de São Paulo, 2003)
A total of 323 patients with lymphadenopathy were selected in Belém, Brazil, between January 1996 and December 2001, and screened for the presence of human herpesvirus-6 (HHV-6) IgM- and- IgG antibodies by enzyme-linked immunosorbent assay (ELISA). When seroprevalence is analyzed by gender, similar rates are found for female (60.6%) and male (55.7%) individuals. Seventy-seven (23.8%) patients were HHV-6-IgM-and- IgG-positive (IgM+ subgroup), with positivity rates of 29.7% and 17.7% (p = 0.0007) for female- and male individuals, respectively. Sera from a subgroup (n = 120) of these subjects, with high HHV-6 antibody levels (either IgM+ or IgG+ reactivities), were subsequently processed for the presence of HHV-6 DNA by polymerase chain reaction (PCR)/nested PCR. Active infections (IgM+ and/or IgG+ high levels specific antibodies plus detection of viral DNA) were diagnosed in 20/77 (20.0%) and 8/43 (18.6%); subgroup of the 120 individuals suspected of having HHV-6 suggestive recent infection. All (n = 28) cases of active infection were found to be associated with HHV-6 variant-A (HHV-6A), as detectable by PCR/nested PCR, using variant-specific primer that amplify regions of 195 base pairs (bp) (HHV-6A) and 423 bp (HHV-6B). Rates of HHV-6 DNA detection between female and male patients were similar (p > 0.05) in the IgM+ and IgG+ groups: 20.4% versus 35.7% and 25.0% versus 13.0%, respectively. HHV-6 DNA was detected across < 5 through 41-50-year age-groups for patients whose serum samples were IgM+, with rates ranging from 7.7% (female subjects aged < 5 years) to 80.0% (male, 11-20 years). Among patients whose serological status was IgG+, HHV-6 DNA was detected in < 5, 6-10, 21-30 and > 50 age-groups at rates that ranged from 15.4% (male, < 5 years of age) to 100.0% (female aged 11-20 years). Swelling cervical lymph nodes were the most common sign, accounting for 9 (32.0%) cases in each gender group. Among patients (n = 28) with active infection by HHV-6A variant, duration of symptoms lasted 1-5 days in 35.7% of subjects, whereas in 64.3% of them the disease lasted 6-20 days. Our data suggest that it is worth seeking for HHV-6 infection whenever a patient (infant or adult) presents with lymphadenopathy as a prominent symptom in the course of an acute febrile illness.